Pemberdayaan Usaha Mikro Getuk Lindri di Desa Cagak Agung Kecamatan Cerme - Fitra Mardiana; Rodhiyah Rodhiyah; Alfi Nugroho (JPM17: Jurnal Pengabdian Masyarakat, 2017)
This aims of this programme are to develop the industry management an increase theproduction of getuk lindri micro industry in Cagak Agung Village , Cerme Gresik. TheSuperficial targets that have been reached are 1) the appropriate technology in theform of getuk lindri mold machine and the colleague can operate it well, 2) thecolleague has the information of serving method and product innovation, 3) thecolleague has the ability to prepare financial bookkeeping administration.The methods that we use in this IbM are 1) traning 2) the guidance of Getuk Lindrimicro industry and 3) monitoring, observing, evaluating and reporting the result. Theimpact of the implementation of this IbM namely the increasing number of productionand how to present the product with a clean and attractive packaging. Key words: Getuk Lindri, teknologi tepat guna